Reducing personal protective equipment waste in the emergency department of a large regional hospital: codesign informed by system science - Mike Forrester; Rebecca Patrick; Steven Allender; Jaithri Ananthapavan; Urvi Thanekar; Hasini Gunasiri; Minoo Naebe; Maryam Naebe (BMJ Public Health)
Background This study aimed to bring together health workers from an emergency department (ED) and broader health system changemakers to cocreate a system-oriented understanding of the drivers of single-use personal protective equipment (PPE) waste, and recommend priority actions for government policy, and organisational change, to reduce PPE waste and transition towards a circular economy approach.Methods Participatory group model building was used with ED and PPE health service stakeholders to create a causal loop diagram of drivers of PPE waste and use this diagram to codesign actions to address this waste. The study setting was an ED of a large regional health service in Victoria, Australia. There were 25 participants including ED doctors, nurses and allied health staff (n=10), sustainability manager (n=1), waste management coordinator (n=1), infection prevention, (n=2) procurement leads, (n=1) external stakeholders (eg, Department of Health, and sustainability authority) (n=3), consumer representatives (n=2), and experts in materials and implementation science (n=2) life-cycle analysis (n=2) and health economics (n=1).Results A causal loop diagram was developed representing the drivers of PPE waste, and codeveloped solutions prioritised by feasibility and impact. Recommendations for priority actions were organised by theme, and at the level of change agent—system/policy level, healthcare organisations and academic organisation. Participants identified five key drivers of single-use PPE waste: (1) centralised state-level procurement processes limited hospital control over reusable or single-use PPE purchasing decisions; (2) lack of clarity of minimum PPE requirements for different clinical scenarios; (3) clinical capacity for cohorting infectious patients in ED; (4) waste management processes not capitalising on recyclable material; and (5) barriers to staff using optimal waste handling processes creating excessive ‘contaminated clinical waste.’ A comprehensive set of recommendations were made by staff to address these issues.Conclusion This study provides new insights into drivers and coproduced potential solutions to the reduction of PPE waste in a hospital ED.